2009
DOI: 10.1109/tnet.2009.2014460
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Channel Probing and Transmission Scheduling for Opportunistic Spectrum Access

Abstract: Abstract-In this study, we consider optimal opportunistic spectrum access (OSA) policies for a transmitter in a multichannel wireless system, where a channel can be in one of multiple states. In such systems, the transmitter typically does not have complete information on the channel states, but can learn by probing individual channels at the expense of certain resources, e.g., energy and time. The main goal is to derive optimal strategies for determining which channels to probe, in what sequence, and which ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 11 publications
0
75
0
Order By: Relevance
“…To obtain such gain, sequential probing based opportunistic channel accessing scheme is proposed, and optimal skipping rule is derived by finite-horizon optimal stopping formulation. More generalized scenarios, e.g., with arbitrary number of channels, statistically non-identical channels, and possibly different probing costs, are studied in seminar work [9], [10], [13]. Moreover, recalling a pre-probed channel as well as accessing an unobserved channel are allowed in their considered communication model.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain such gain, sequential probing based opportunistic channel accessing scheme is proposed, and optimal skipping rule is derived by finite-horizon optimal stopping formulation. More generalized scenarios, e.g., with arbitrary number of channels, statistically non-identical channels, and possibly different probing costs, are studied in seminar work [9], [10], [13]. Moreover, recalling a pre-probed channel as well as accessing an unobserved channel are allowed in their considered communication model.…”
Section: Related Workmentioning
confidence: 99%
“…The sequential accessing control problem is firstly studied in multiple i.i.d Rayleigh channels scenario [8], where a multichannel opportunistic auto rate protocol is proposed. Further, more generalized scenarios allowing users to recall pre-probed channels [9], [10] or considering the activities of primary users [11], [12] are further studied. The major concern in these studies is to balance exploration and exploitation on temporary channel status.…”
mentioning
confidence: 99%
“…In [9], optimal opportunistic spectrum access (OSA) policies for a transmitter in a multichannel wireless system is considered. The channel states can be learned by probing individual channels at the expense of certain resources, e.g., energy and time.…”
Section: Related Workmentioning
confidence: 99%
“…In [2], [3], Deng et al presented a queue model for analyzing random access multi-channel MAC scheme (without diversity gain) and concluded that multichannel MAC scheme would not improve either delay or throughput performance compared to single channel MAC. In [1], [5], [9], opportunistic channel selection algorithms were investigated with system performance evaluated experimentally and mathematically. There however lacked a general model for analyzing the delay performance of these strategies.…”
Section: Related Workmentioning
confidence: 99%
“…In the opportunistic multi-channel MAC scheme, we assume that the pair of sender/receiver is able to evaluate the channel quality after a certain amount of channel sensing delay and to choose the best one for data communication. We consider three settings: (1) an ideal scenario where no control channel is needed and no sensing delay is incurred, (2) a more realistic scheme where users compete for access on a control channel using random access, and (3) a scheme similar to (2) but with a Time Division Multiplex (TDM) based access scheme on the control channel. Our analysis show that in terms of delay performance, the random access overhead on the control channel almost always wipe out the channel diversity gain, which is the main motivation behind an opportunistic multi-channel MAC.…”
mentioning
confidence: 99%